2020
DOI: 10.3762/bjoc.16.99
|View full text |Cite
|
Sign up to set email alerts
|

The charge-assisted hydrogen-bonded organic framework (CAHOF) self-assembled from the conjugated acid of tetrakis(4-aminophenyl)methane and 2,6-naphthalenedisulfonate as a new class of recyclable Brønsted acid catalysts

Abstract: The acid–base neutralization reaction of commercially available disodium 2,6-naphthalenedisulfonate (NDS, 2 equivalents) and the tetrahydrochloride salt of tetrakis(4-aminophenyl)methane (TAPM, 1 equivalent) in water gave a novel three-dimensional charge-assisted hydrogen-bonded framework (CAHOF, F-1). The framework F-1 was characterized by X-ray diffraction, TGA, elemental analysis, and 1H NMR spectroscopy. The framework was supported by hydrogen bonds between the sulfonate anions and the ammonium cations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
2
17
1
Order By: Relevance
“…83 Similarly, for a recently reported charge-assisted HOF, F-1a, the presence of catalytically active Brønsted acid sites makes it an excellent heterogeneous catalyst to catalyze the ring-opening of epoxides and the Diels−Alder reaction between cyclopentadiene and methyl vinyl ketone. 113 ■ BIOLOGICAL APPLICATIONS Since most HOFs are metal-free, they exhibit considerable biocompatibility and low toxicity, thus being excellent candidates for biological applications. As mentioned above, using a pyrene-based linker, Yin et al reported the synthesis of a highly stable HOF, PFC-1 (Figure 8a).…”
Section: ■ Fluorescent Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…83 Similarly, for a recently reported charge-assisted HOF, F-1a, the presence of catalytically active Brønsted acid sites makes it an excellent heterogeneous catalyst to catalyze the ring-opening of epoxides and the Diels−Alder reaction between cyclopentadiene and methyl vinyl ketone. 113 ■ BIOLOGICAL APPLICATIONS Since most HOFs are metal-free, they exhibit considerable biocompatibility and low toxicity, thus being excellent candidates for biological applications. As mentioned above, using a pyrene-based linker, Yin et al reported the synthesis of a highly stable HOF, PFC-1 (Figure 8a).…”
Section: ■ Fluorescent Sensingmentioning
confidence: 99%
“…In addition, 1-Ni can also be used for catalyzing the asymmetric F–C alkylations of indole and aryl aldimines . Similarly, for a recently reported charge-assisted HOF, F-1a, the presence of catalytically active Brønsted acid sites makes it an excellent heterogeneous catalyst to catalyze the ring-opening of epoxides and the Diels–Alder reaction between cyclo­pentadiene and methyl vinyl ketone …”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Meanwhile, the diversity of hydrogen bonds provides more possibilities for the construction of the frameworks of crystalline organic salts. [48][49][50][51][52][53][68][69][70][71] A series of guanidinium sulfonate (GS) frameworks with various elegant and diversified architectures, like lamellar, cylindrical, and cubic ( Figure 5), have been synthesized from guanidinium cations and organosulfonate anions through salt bridges by Ward and co-workers. [48][49][50][51][52][53] These crystalline organic salts were achieved by rational design of the size and the symmetry of the tectons and assembly.…”
Section: Organic Acid Tecton With Sulfonate Groupmentioning
confidence: 99%
“…Meanwhile, the diversity of hydrogen bonds provides more possibilities for the construction of the frameworks of crystalline organic salts. [ 48–53,68–71 ]…”
Section: Crystalline Porous Organic Saltsmentioning
confidence: 99%
“…[ 14‐16 ] To achieve this goal, constructing the charge‐assisted hydrogen bonding organic networks (CAHONs) with oppositely charged components and multiple hydrogen‐bonding interactions has considered as a powerful strategy by virtue of the electrostatic interactions between discrete cations and anions. [ 2,17‐19 ] However, the research on CAHONs is still rare, so we urgently need to synthesize more CAHONs and explore their potential properties in depth.…”
Section: Background and Originality Contentmentioning
confidence: 99%